* Outcomes following acute variceal bleeding in the 2007 UK national audit. (13th March 2011) - Jairath, V; Logan, R; Hearnshaw, S; Kahan, B; Travis, S; Murphy, M; Palmer, K
Abstract : Introduction: Most outcome data following acute variceal haemorrhage (AVH) come from centres of expertise which may not reflect 'real-life' outcomes. Methods: To describe clinical characteristics and outcomes of patients presenting with AVH throughout the UK. The authors analysed data from the 2007 UK Comparative Audit of Upper Gastrointestinal Bleeding 1 . In this study prospective data were collected on consecutive patients presenting to 208 UK hospitals with all cause AUGIB between 1 May and 30 June 2007. Here the authors describe patients who presented with AVH. Results: 599/6750 (8.9%) presenting with AUGIB had known cirrhosis. 88% (526/599) of these presented with variceal bleeding and 12% (73/599) with non-variceal bleeding. 86% (452/526) of those with AVH were acute admissions (median age 53 years; IQR 46–63, 68% male). Before admission 8% (43/526) were taking aspirin, 4% (19/526) warfarin and 4% (22/526) NSAIDS. Median MELD score on admission was 15 (IQR 11–20). Prior to endoscopy 57% (299/526) received an intravenous PPI, 44% (232/526) vasopressin (or analogue), 27% (144/526) antibiotics and 2% (11/526) tranexamic acid. 62% (328/526) presented outside normal working hours (OOH). For endoscopy, 30% (157/526) were performed OOH and 66% (346/526) within 24 h of presentation, with 12% (65/526) under general anaesthetic. 80% (418/526) had oesophageal varices and 11% (59/426) gastric varices as the source of bleeding, but just 64% (339/526) had a therapeutic procedure at the index endoscopy. 30% (162/526) underwent a repeat endoscopy. 5% (30/526) had a Sengstaken-Blakemore tube inserted and 4/526 (0.8%) patients underwent TIPSS. 26% (135/526) had rebleeding during admission and 15% (80/526) died. The median length of stay was 9 days (IQR 5–21 days). AUROC analysis showed that the admission MELD score usefully predicted mortality (AUROC 0.78), but poorly predicted the need for therapeutic endoscopy or rebleeding risk. The clinical Rockall score was a poor predictor of mortality, need for therapeutic intervention at endoscopy or rebleeding risk (AUROC 0.64, 0.52 and 0.61 respectively). Conclusion: Mortality following AVH may have improved in recent years, but notable deficiencies in the timeliness and use of endoscopic intervention for AVH persist. The admission MELD best predicted mortality. The Rockall score was not a useful predictor of clinically important outcomes following AVH.